A novel harmonic elimination method for a three-phase diode rectifier with controlled DC link current - Zare, Firuz (2014)
© 2014 IEEE. Conventional diode rectifiers generate current harmonics which affects quality of power systems. According to the IEC61000 standards, different harmonic limits have been defined for broad range of products in which they have to fulfill the regulations. A cost effective solution to reduce current harmonic emission in low power motor drive systems (below 10 kW) is to use passive filters such as DC or AC chokes; but they are bulky and expensive filters and also input current Total Harmonic Distortion (THD) value depends on load profile. This paper presents an active harmonic mitigation technique with a novel current modulation method for three phase motor drive systems. Analysis and simulations have been carried out to verify the proposed method.